Effect of pressure and defects on the pipe flattening factor. (December 2018) - Edjeou, W.; Pluvinage, G.; Capelle, J.; Azari, Z.
Abstract: Starting from an actual case of an oil pipe exhibiting significant ovalization, maximum admissible flattened factor fad proposed by codes (3%) is discussed. The weak point of this rule is its geometric character. It is shown that the fad decreases with pressure and with geometrical defects. It is not very sensitive to the bent shape of the pipe, or the location between ovalization and orientation supports. A simple elastic model based on a safety factor of two (2) is proposed Highlights: Harmfulness of 8.8% ovalization in a pipe build during the 60′ and laying at the bottom of an US Great lake is examined. It has been seen that for this ovalization the local stress exceeds the yield stress. Code criterion of 3% of ovalization corresponds to a safety factor of 2 on yield stress.